FORMATIVE ASSESSMENT AND THE INTERACTION BETWEEN TO AND RRS IN MATHEMATICS TEACHING - Adeilton de Oliveira Andrade, Emanuel (Journal of Interdisciplinary Debates, 2023)
This article investigates how Formative Assessment can be influenced by Objectification Theory (OT) and how alternatives to traditional assessment can consider the ethical and subjective development of students. The analysis is carried out in the context of mathematics teaching in the 7th grade of Elementary School, focusing on the relationships between OT and RRS. To achieve this goal, we have outlined specific objectives that include the analysis of existing assessment practices, the proposition of training strategies, the incorporation of RRS in assessment, and the assessment of the impact of these practices on students’ cognitive and affective development. The case study fulfilled its objective by proposing alternatives for formative evaluation activities.